Chloride and organic osmolytes: a hybrid strategy to cope with elevated salinities by the moderately halophilic, chloride‐dependent bacterium Halobacillus halophilus. (14th May 2012) - Saum, Stephan H.; Pfeiffer, Friedhelm; Palm, Peter; Rampp, Markus; Schuster, Stephan C.; Müller, Volker; Oesterhelt, Dieter
Summary: Salt acclimation in moderately halophilic bacteria is the result of action of a grand interplay orchestrated by signals perceived from the environment. To elucidate the cellular players involved in sensing and responding to changing salinities we have determined the genome sequence of Halobacillus halophilus, a Gram‐positive moderate halophilic bacterium that has a strict requirement for the anion chloride. Halobacillus halophilus synthesizes a multitude of different compatible solutes and switches its osmolyte strategy with the external salinity and growth phase. Based on the emerging genome sequence, the compatible solutes glutamate, glutamine, proline and ectoine have already been experimentally studied. The biosynthetic routes for acetyl ornithine and acetyl lysine are also delineated from the genome sequence. Halobacillus halophilus is nutritionally very versatile and most compatible solutes cannot only be produced but also used as carbon and energy sources. The genome sequence unravelled isogenes for many pathways indicating a fine regulation of metabolism. Halobacillus halophilus is unique in integrating the concept of compatible solutes with the second fundamental principle to cope with salt stress, the accumulation of molar concentrations of salt (Cl ‐ ) in the cytoplasm. Extremely halophilic bacteria/archaea, which exclusively rely on the salt‐in strategy, have a high percentage of acidic proteins compared with non‐halophiles with a low percentage. Halobacillus halophilus has an intermediate position which is consistent with its ability to integrate both principles.